Final step on 'Sum of Gaps'

Calculus Level 5

Define a m + 1 , n = k = 1 n ( a m , k b m ) and b m + 1 = lim n a m + 1 , n where m 0 \displaystyle a_{m+1,n} = \sum_{k=1}^{n} \left(a_{m,k} - b_m\right) \text{ and} \,\,\, b_{m+1} = \lim_{n \to \infty} a_{m+1,n} \text{where}\,\,\, m\ge 0

a 0 , k = ( 1 ) k + 1 k and b 0 = 0 \displaystyle a_{0,k} = \frac{\left(-1\right)^{k+1}}{k} \text{ and}\,\,\, \displaystyle b_{0} = 0

It is well-known that b 1 = ln 2 \displaystyle b_1 = \ln{2}

The value of b 2 b_2 and b 3 b_3 has been found at this problem and this problem respectively.

Now A = k = 1 b k \displaystyle A = \sum_{k=1}^{\infty} b_k .

What is the value of 1000 A , \displaystyle\left\lfloor 1000A \right\rfloor, where \lfloor \cdot \rfloor denotes the floor function ?


The answer is 1000.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Nov 11, 2018

It is a simple induction to show that a m , n = 0 1 x m 1 ( 1 ( x ) n ) ) ( 1 + x ) m d x b m = 0 1 x m 1 ( 1 + x ) m d x a_{m,n} \; = \; \int_0^1 \frac{x^{m-1}\big(1 - (-x)^n)\big)}{(1+x)^{m}}\,dx \hspace{2cm} b_m \; = \; \int_0^1 \frac{x^{m-1}}{(1+x)^{m}}\,dx for all m , n 1 m,n \ge 1 , and hence A = m = 1 b m = m = 1 0 1 x m 1 ( 1 + x ) m d x = 0 1 d x = 1 A \; = \; \sum_{m=1}^\infty b_m \; = \; \sum_{m=1}^\infty \int_0^1 \frac{x^{m-1}}{(1+x)^m}\,dx \; = \; \int_0^1 \,dx \; = \; 1 making the answer 1000 \boxed{1000} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...